Evaluating drugstore geographic accessibility in the barangays of region 4B: a mapping study of FDA- registered drugstores - Advincula, Arnina Jenien D.
Despite the presence of national policies that aim to to bridge the gaps in healthcare, especially in underserved areas of the Philippines, most areas in Region 4B are still found to have fair to no accessible health care facilities and services. The study aims to evaluate the accessibility of FDA-registered drugstores in the barangays of MIMAROPA and analyze its relationship with key socioeconomic factors Socioeconomic characteristics of barangays within the region were obtained from relevant online reports generated by government agencies. Drugstore locations, geospatial patterns, distances from other public healthcare facilities, and pharmacy densities were derived using these data. The relationship between pharmacy density and characteristics was also examined using multiple linear regression. Majority of the barangays in the region were classified as non-GIDA, rural, income class 1, and with an average population of 2211. There are around 1 drugstore per 3 barangays, and these drugstores are found to be highly clustered across all provinces and found within 5 km from the barangays on average. Barangay and RHU-to-drugstore distances are less than 5 km in most provinces, while barangay-to-RHU distances exceed in all provinces. Overall, the travel time and distances between facilities follow a positively-skewed distribution. Regional median pharmacy density is at 0 per 10,000 population in the barangay level. Mean density at the municipal level ranged from 0.99 to 1.68 across provinces but with some municipalities recorded at 0. Among the socioeconomic factors, GIDA status and urban classification were identified as significant predictors of pharmacy density. xi The overall findings highlight a stark disparity in terms of pharmacy accessibility across MIMAROPA. The government should prioritize expanding drugstore coverage, particularly encouraging the establishment of pharmacies in GIDAs and other rural communities.